The influence of environmental enrichment with different kind of wood on carcass quality of individually caged rabbits - Kermauner, Ajda (Acta agriculturae slovenica. Suplement, 2004)
The influence of addition of different types of wooden sticks as gnawing material for environmental enrichment on the carcass traits was studied on 48 male New Zealand White rabbits of Slovenian male line SIKA. Animals were housed individually in wire cages equipped with feeder and nipple drinkers. Feed and water were available ad libitum, the duration of lighting was 12 hours. According to the tzpe of wood placed in the cage, rabbits were equally allotted to four groups: control, oak, lime and Norway spruce. The experiment lasted from 38th day of age to 103rd day, when rabbits were slaughtered and carcass traits were measured. Twenty-four hours after slaughter the pH value and colour of meat were recorded. The addition of wooden stick to wire cages had no important influence on carcass characteristics. Among three enriched groups with different kind of wood only meat of rabbits with spruce stick partly exhibited different colour: meat from SPRUCE group had darker colour (CIE L*: 57.05) than from OAK (59.40) and LIME (59.71) groups and less red (a*: 3.73) and in tendency less yellow colour (b*: 1.10) than meat from OAK group (a*: 4.66, b* 1.96).
Keywords: glodanje; klavna kakovost; kletke; kunci; kvaliteta; les; meso; okolje